High temperature oxidation behaviors of Ir-Ni-Ta-(B) metallic glass. (15th August 2022) - Han, Fei; Chen, Yanan; Liu, YanHui; Yang, Xiaodong; Che, Shenglei; Zhang, Yan; Huo, Juntao; Gao, Meng; Wang, Jun-Qiang
Abstract: Due to the limited surface structure of optical device, the mold materials are extremely difficult to be processed at micro-nano scale, especially considering high temperature oxidation. Ir-Ni-Ta-(B) metallic glasses become the optimal candidate for the molding materials of optical devices. In this work, the high temperature oxidation behaviors for Ir-Ni-Ta-(B) during the isothermal and continuous heating process were studied. It is found that the addition of boron can enhance the oxidation resistance of Ir-Ni-Ta. What is more, Ir-Ni-Ta-(B) has formed a unique four-layer structure. This study reveals the oxidation mechanism and provides new insights into the development of new materials. Highlights: High temperature oxidation behaviors of Ir-Ni-Ta-(B) metallic glasses are studied. Oxidation resistance of Ir-Ni-Ta metallic glass is greatly improved by adding boron. Ir-Ni-Ta-(B) metallic glasses form a unique four-layer oxide structure. Pre-annealing treatment is proposed to improve oxidation resistance of metallic glass.